Selective localization of titanium dioxide nanoparticles at the interface and its effect on the impact toughness of poly(L-lactide)/poly(ether)urethane blends - Q. Fu; H. W. Bai; H. Xiu; C. M. Huang; C. L. Xu; X. Y. Li (eXPRESS Polymer Letters)
Inorganic nanofillers are often added into polymer/elastomer blends as a third component to modify their performance. This work aims to clarify the role of interface-localized spherical nanoparticles in determining the impact toughness of polymer blends. The selective distribution of titanium dioxide (TiO2) nanoparticles in poly(L-lactide)/poly(ether) urethane (PLLA/PU) blends was investigated by using scanning electron microscope. It is interesting to find that, regardless of the method of TiO2 introduction, nano-TiO2 particles are always selectively localized at the phase interface between PLLA and PU, leading to a significant improvement in notched Izod impact toughness. The moderately weakened interfacial adhesion induced by the interfacially-localized nano-TiO2 particles is believed to be the main reason for the largely enhanced impact toughness.